Waterborne exposure to microcystin-LR alters thyroid hormone levels, iodothyronine deiodinase activities, and gene transcriptions in juvenile zebrafish (Danio rerio). (February 2020) - Hu, Qing; Liu, Zidong; Gao, Yu; Jia, Dan; Tang, Rong; Li, Li; Li, Dapeng
Abstract: This study investigated the effects of microcystin (MC) on the regulation of thyroid hormone (TH) metabolism in juvenile zebrafish exposed to MC-LR. The results showed that acute MC-LR exposure at concentrations ranging from 50 μg/L to 400 μg/L led to significant reductions in thyroxine (T4 ) and triiodothyronine (T3 ) levels in juvenile zebrafish. The transcription levels of genes involved in TH synthesis, such as corticotropin-releasing hormone ( crh ), thyroid-stimulating hormone ( tsh ), thyroid peroxidase ( tpo ) and transthyretin ( ttr ), were significantly decreased followed by an increase after MC-LR exposure. Transcription of the TH nuclear receptors ( tr-α and tr-β ) was significantly reduced during the exposure period. Moreover, the activities of iodothyronine deiodinase type Ⅰ (ID1) and iodothyronine deiodinase type Ⅱ (ID2) showed initially decreased and then increased trend, while the activity of iodothyronine deiodinase type Ⅲ (ID3) significantly decreased during MC-LR exposure. In addition, the effect of MC-LR on deiodinase activities and T4 contents were important causes of the decreased T3 at the early exposure stage. These results indicated that acute MC-LR exposure significantly interfered with the transcription of genes related to TH synthesis, transport and metabolism, and affected normal function of the thyroid which leads to decrease of T4 and T3 in juvenile zebrafish. Therefore, the thyroid function is susceptible to interference by MC-LR, and it may cause adverse effects on the growth and development of juvenile zebrafish. Highlights: MC-LR exposure significantly decreased the T4 and T3 levels in juvenile zebrafish. MC-LR could alter gene transcription and IDs activities in the HPT axis. A compensatory mechanism can be triggered to maintain TH homeostasis in juvenile zebrafish.